Validation of a metabolite–GWAS network for Populus trichocarpa family 1 UDP-glycosyltransferases - Saint-Vincent, Patricia M. B.; Furches, Anna; Galanie, Stephanie; Teixeira Prates, Erica; Aldridge, Jessa L.; Labbe, Audrey; Zhao, Nan; Martin, Madhavi Z.; Ranjan, Priya; Jones, Piet; Kainer, David; Kalluri, Udaya C.; et al. (Frontiers in Plant Science, 2023)
Metabolite genome wide association studies (mGWAS) are increasingly used to discover the genetic basis of target phenotypes in plants such as Populus trichocarpa, a biofuel feedstock and model woody plant. Despite their growing importance in plant genetics and metabolomics, few mGWAS are experimentally validated. Here, we present a functional genomics workflow for validating mGWAS-predicted enzyme-substrate relationships. We focus on uridine diphosphate- glycosyltransferases (UGTs), a large family of enzymes that catalyze sugar transfer to a variety of plant secondary metabolites involved in defense, signaling, and lignification. Glycosylation influences physiological roles, localization within cells and tissues, and metabolic fates of these metabolites. UGTs have substantially expanded in P. trichocarpa, presenting a challenge for large- scale characterization. Using a high-throughput assay, we produced substrate acceptance profiles for 40 previously uncharacterized candidate enzymes. Assays confirmed 10 of 13 leaf mGWAS associations, and a focused metabolite screen demonstrated varying levels of substrate specificity among UGTs. A substrate binding model case study of UGT-23 rationalized observed enzyme activities and mGWAS associations, including glycosylation of trichocarpinene to produce trichocarpin. We identified UGTs putatively involved in lignan, flavonoid, and phytohormone metabolism, with potential implications for cell wall biosynthesis, nitrogen uptake, and biotic and abiotic stress response. Our results provide new support for in silico analyses and evidence-based guidance for in vivo functional characterization.